The Role of Customer Satisfaction as A Mediator In The Influence of Game Habits, Event Marketing, and Perceived Price Fairness on Customer Loyalty Among Pubg Mobile Players in Indonesia. - Rivelino, Nicholas; Pebrianti, Wenny; Listiana, Erna; Setiawan, Harry (Economics and Digital Business Review, 2026)
The rapid development of the mobile gaming industry has made PUBG Mobile one of the most popular games in Indonesia. However, in recent years, the game has faced a decline in in-app purchases and a potential decline in player loyalty. This study aims to analyze the influence of Game Habits, Event Marketing, and Perceived Price Fairness on Customer Loyalty, with Customer Satisfaction as a mediating variable, on PUBG Mobile users in Indonesia. The research model is based on the post-adoption behavior framework and customer loyalty theory, which emphasizes that satisfaction is a key mechanism in shaping user continuance intentions and loyalty. An online survey was conducted on 200 active PUBG Mobile players who had played for at least the past three months and had participated in in-game events. Data were analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method. The results show that Game Habits, Event Marketing, and Perceived Price Fairness have a positive and significant effect on Customer Satisfaction and Customer Loyalty. Furthermore, the mediation test confirmed that Customer Satisfaction significantly mediated the influence of the three variables on Customer Loyalty, in line with Expectation–Confirmation Theory and Oliver's loyalty model, which places satisfaction as a prerequisite for loyalty. These findings confirm that consistent playing habits, the quality of in-game event experiences, and the perceived fairness of virtual item prices are key factors in building player satisfaction and loyalty. This research provides practical implications for game developers in designing experience-based marketing strategies and fair pricing policies to retain a long-term player base amidst the increasingly competitive mobile gaming industry.